2018
DOI: 10.1038/s41531-018-0071-3
|View full text |Cite
|
Sign up to set email alerts
|

Safety and tolerability of IRL790 in Parkinson’s disease with levodopa-induced dyskinesia—a phase 1b trial

Abstract: IRL790 is a novel compound with psychomotor stabilizing properties primarily targeting the dopamine D3 receptor. IRL790 is developed as an experimental treatment for levodopa-induced dyskinesia (LID), impulse control disorder, and psychosis in Parkinson’s disease (PD). The primary objective was to investigate the safety and tolerability of IRL790 in PD patients with LID in a randomized controlled trial. PD patients with peak-dose dyskinesia were randomized to placebo or IRL790 treatment (1:3 ratio) for 4 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 16 publications
(17 reference statements)
2
15
0
Order By: Relevance
“…They have also been suggested to have greater sensitivity to detect subtle clinical changes 29,30 and were included as a novel feature in our trial protocol because of this possibility. To our knowledge, this study is among the first few RCTs in PD using wearable sensor data as outcome measures 31 . This is also the only study of HP eradication in PD to investigate, a priori, the possible role of concomitant SIBO.…”
Section: Discussionmentioning
confidence: 99%
“…They have also been suggested to have greater sensitivity to detect subtle clinical changes 29,30 and were included as a novel feature in our trial protocol because of this possibility. To our knowledge, this study is among the first few RCTs in PD using wearable sensor data as outcome measures 31 . This is also the only study of HP eradication in PD to investigate, a priori, the possible role of concomitant SIBO.…”
Section: Discussionmentioning
confidence: 99%
“… 125 A phase Ib study with mesdopetam as an adjunct treatment to regular antiparkinsonian medication in 15 PD patients experiencing peak-dose dyskinesia showed a median UDysRS score reduction of 11.5 points vs placebo. 126 In 2019, a randomized, double-blind, placebo-controlled, multicenter phase IIa study on the efficacy and tolerability of mesdopetam was carried out in 74 PD patients with LID on stable antiparkinsonian medication (ClinicalTrials.gov identifier: NCT03368170). The study showed a meaningful reduction in LID severity as assessed by UDysRS, UPDRS part IV, and patient-reported diaries (Hauser diaries), and no side effects were reported.…”
Section: Experimental Pharmacological Therapies For Lid In Pd Patientsmentioning
confidence: 99%
“…IRL790 is developed for treatment of complications associated with therapy in PD, primarily LIDs. In fact, there is preliminary data that IRL790 counteracts LIDs in PD patients (Svenningsson et al, 2018), and IRL790 shows clear antidyskinetic effects in rats (Waters et al, 2020). Studies have reported a higher mortality rate toward dopaminergic lesioning by 6-hydroxydopamine in mice than rats (Lundblad et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…IRL790 is developed for treatment of complications associated with therapy in Parkinson disease (PD). It is safe and tolerable in PD patients and appears to counteract levodopa-induced dyskinesias (LIDs) (Svenningsson et al, 2018). IRL790 is currently in a clinical phase 2 efficacy study for LID in PD.…”
Section: Introductionmentioning
confidence: 99%